The odds that working women will accept cervical cancer screening and HPV vaccination - Nwose, Ezekiel Uba; Okwe, Uchechukwuka Nnemdi; Chime, Helen (International Journal of Research in Medical Sciences, 2019)
Background: Factors influencing acceptance of cervical cancer services are being investigated, and widely reported to be quite low. However, there is dearth of research investigation on the odds of women’s acceptance of this gynaecological service. Objective of this study was to investigates the odds of unwilling to accept cervical cancer services. Methods: The study was a questionnaire-based cross-sectional survey and fourth piece in a series of analysis. Details of data collection are as previously described. Odds ratio was determined using online calculator; and based on proportion of respondents who have accepted the cervical cancer service, willing to complete an incomplete process and encourage others to take up the procedure. Results: The percentage of respondents who indicated no problem with HPV vaccination (55%) is higher than cervical screening (53%), but not statistically significantly different. On average, unwillingness to vaccinate later, complete their vaccinations or encourage their daughter are one-third of those who vaccinated. Those unwilling to take up cervical screening, encourage others to screen or overcome their fears are more than (161%) the subgroup who have been screened. Results show odds of unwillingness for both procedures are less than 1, but a little greater for cervical screening. Conclusions: It has been articulated that the likelihood to take up cervical cancer services will be influenced by the beliefs. This report advances that observed low acceptance level does not translate to high likelihood of unwillingness to accept the gynaecological services. Belief and nature of work of women need to be concertedly investigated.